SMKI Perencanaan Keamanan Sistem Informasi Terpadu (SITU) - Hendrik, Dede (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2024)
With the rapid development of technology, all institutional, government and other sectors have used technology as a medium to make it easier to process data and information. No less important in the field of education, especially universities, everyone already uses a system to manage student and other data. In this way, the developer helps this information service by creating a website, namely the Integrated Information System (SITU). After several years, the benefits of SITU have been recognized by the community and universities can be said to be quite helpful in providing information services both from an academic perspective. After a long time SITU has been used as a medium for information and transactions, it turns out that SITU has several threats which are expected to hinder public services from accessing SITU, for example: natural disasters, building damage, human error, the actions of irresponsible people (Hackers). etc. So we think that all of this can be detrimental to universities. With the possibility of these threats or weaknesses occurring, the author tries to analyze, study and plan to minimize the possibility of this happening, by creating a Higher Education Integrated Information System (SITU) Information Security Plan. With ISO/IEC 27001:2005 standards